2021
DOI: 10.1002/hep.32101
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacologic activation of hepatic farnesoid X receptor prevents parenteral nutrition–associated cholestasis in mice

Abstract: after first online publication: In the Abstracts "dextran sodium sulfate" was corrected to "dextran sulfate sodium"; In the caption for Figure 7D, the words "GW4064 and" and "untreated and" appeared in the published article and are now removed. We apologize to the authors and our readers for these errors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 41 publications
(123 reference statements)
3
26
0
Order By: Relevance
“…12,14 Recently, a new model of PNAC has been developed that combines 75% intestinal resection and PN in 7-10 day old piglets. 44 In agreement with our murine studies, in this model gut Nr1h4 (FXR) is suppressed, 17 whereas in the DSS-PN/Inflix group, we find a direct correlation between decreased hepatic expression of Cyp7a1 with elevated hepatic Fgfr4 expression, in the piglet model of complete ileal and ileocecal valve resection, hepatic Cyp7a1 expression was increased corresponding to decreased gut FGF19 expression, the latter presumably the result of resection of the ileum (which is where FGF19 is expressed) and absence of enteral feedings. It should be noted that in most infants and adults with SBS, absence of the ileum is rare.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…12,14 Recently, a new model of PNAC has been developed that combines 75% intestinal resection and PN in 7-10 day old piglets. 44 In agreement with our murine studies, in this model gut Nr1h4 (FXR) is suppressed, 17 whereas in the DSS-PN/Inflix group, we find a direct correlation between decreased hepatic expression of Cyp7a1 with elevated hepatic Fgfr4 expression, in the piglet model of complete ileal and ileocecal valve resection, hepatic Cyp7a1 expression was increased corresponding to decreased gut FGF19 expression, the latter presumably the result of resection of the ileum (which is where FGF19 is expressed) and absence of enteral feedings. It should be noted that in most infants and adults with SBS, absence of the ileum is rare.…”
Section: Discussionsupporting
confidence: 88%
“…14 Antibiotic suppression of intestinal microbiota, abrogation of macrophage recruitment, activation of FXR, as well as blockade of LPS or IL1 signaling in the mouse model all attenuated PNAC and restored Abcc2 and Abcb11 transcription. 12,14,17 Here, we mechanistically linked inflammatory signals with cholestasis in the PNAC mouse model and demonstrate that TNFαα directly suppressed expression of hepatocellular bile transporters Abcc2, Abcb11, Abcg5, and Abcg8 in vivo and in vitro in both human hepatoma cell lines and primary mouse hepatocytes. Genetic or pharmacological blockade of TNF signaling protected mice from PNAC through preventing bile transporter downregulation.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…33,34 Available studies support the hypothesis that altered FXR signaling is important in the onset of parenteral nutritionassociated cholestasis. 35,36 Moreover, serum FGF19 concentration was associated with hepatic portal inflammatory and fibrotic liver changes in patients with pediatric intestinal failure. 6 Our proteomic results indicated that FXRa (Nr1h4, foldchange ¼ 0.76) was downregulated in patients with PNAHS (Supplementary Data 1), and cholesterol 7a-hydroxylase (CYP7A1; fold-change ¼ 3.08) and sterol 12a-hydroxylase (CYP8B1; fold-change ¼ 1.52), which are the rate-limiting enzymes in the conversion of cholesterol to primary bile acids, were strongly upregulated in patients with PNAHS (Supplementary Data 1).…”
Section: Hepatic Knockdown Of Pp2a-ca Suppresses Hepatic Fatty Acid B...mentioning
confidence: 99%